Review on Islamic Empowerment Model - Sanrego, Yulizar Djamaluddin; Taufiq, Muhammad (Tamkin Journal, 2023)
This study aims to see the development of research on the topic of Islamic empowerment model and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Islamic Empowerment Model" which comes from the Dimension database with a total of 442 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Islamic Empowerment Model" research development in the world. The results of the study found that based on bibliometric keyword mapping, there are 3 clusters that can become research paths with topics related to Community and Islamic Empowerment Model, Covid-19 Pandemic and Islamic Empowerment Model, and Issues in the Islamic Empowerment Model. Furthermore, the most used words are pesantren, student, women, person, society, and economy Empowerment